Accuracy of two plasma antibody tests and faecal antigen test for non-invasive detection of H. pylori in middle-aged Caucasian general population sample. (3rd July 2018) - Skrebinska, Sabine; Daugule, Ilva; Santare, Daiga; Isajevs, Sergejs; Liepniece-Karele, Inta; Rudzite, Dace; Kikuste, Ilze; Vanags, Aigars; Tolmanis, Ivars; Atstupens, Juris; Park, Jin Young; Herrero, Rolando; et al.
Abstract: Objective: The aim of the study was to assess the accuracy of two plasma Helicobacter pylori (H. pylori) antibody test-systems and a stool antigen test (SAT) system in a general population sample in Latvia. Materials and methods: Blood and faecal samples were analysed in healthy individuals (40–64 years), referred for upper gastrointestinal endoscopy according to pilot study protocol within a population-based study investigating gastric cancer prevention strategies (GISTAR pilot study). Antibodies to H. pylori were assessed in plasma by latex-agglutination test and enzyme-linked immunosorbent assay (ELISA). H. pylori antigen in faecal samples was detected by a monoclonal enzyme immunoassay-based SAT. Histological assessment of H. pylori based on a modified Giemsa staining method was used as the gold standard. Individuals having received H. pylori eradication within one year prior to enrolment were excluded. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and overall accuracy were calculated. Receiver-operating characteristic curves were designed to estimate the optimal diagnostic cut-off value of tests. Results: The analysis included 779 participants for latex-agglutination test, 1002 for ELISA and 672 individual samples for SAT. The sensitivity, specificity, PPV, NPV and overall accuracy were as follows: latex-agglutination test (86;81;87;80;84%), ELISA (97;72;83;94;86%) and SAT (87;81;87;81;85%), respectively. The optimal diagnostic cut-off value for ELISA test was ≥50.26 g/L. Conclusions: Although the performance of the three tests was comparable to each other, the three test systems showed suboptimal accuracy, with important implications for public health programs based on 'test-and-treat' strategy.